Family Roles as Family Functioning Regulators - Stepanyan, Armine (Տիգրան Մեծ)
The author examines the problems related to the formation and functioning of family roles. Having social roots, family roles appear at the individual level by performing the social function of the family formation as a social institute.
Keywords: Social philosophy; Psychology